Role of Arbuscular Mycorrhizal Fungi in Maintaining Sustainable Agroecosystems - Anju Chaudhary; Shital Poudyal; Amita Kaundal (Applied Microbiology)
Arbuscular mycorrhizal (AM) fungi play a crucial role in maintaining sustainable agroecosystems by forming mutualistic relationships with plant roots, improving soil health, facilitating nutrient uptake, and enhancing resilience to abiotic stresses. The mutualistic relationship between AM fungi and plants promotes a balanced microbial community and improves soil structure by forming stable soil aggregates. Additionally, AM fungi can lower the adverse effects of high soil phosphorus (P) while also enhancing plant tolerance to drought, salinity, and heavy metal toxicity through osmotic regulation and antioxidant production. Arbuscular mycorrhizal fungi also support beneficial microorganisms, such as potassium (K)-solubilizing microbes and nitrogen (N)-transforming bacteria, which enhance the nutrient dynamics in soil. However, intensive agricultural practices, including heavy tillage and continuous monoculture, disrupt AM fungal networks and reduce microbial diversity, impairing their effectiveness. Adopting conservation practices such as reduced tillage, crop rotation, and organic amendments supports AM fungal growth. Incorporating mycorrhizal crops and utilizing native fungal inoculants can enhance AM fungal colonization and plant growth. These strategies collectively bolster soil health, crop productivity, and resilience, offering a promising solution to the environmental and agricultural challenges posed by intensive farming. By promoting AM fungi growth and colonization, agroecosystems can achieve long-term productivity and increased sustainability.